A kernelised fuzzy-Support Vector Machine CAD system for the diagnosis of lung cancer from tissue images. (15th May 2008) - Land, Walker H.; McKee, Daniel W.; Zhukov, Tatyana; Song, Dansheng; , Wei Qian
This research describes a non-interactive process that applies several forms of computational intelligence to classifying biopsy lung tissue samples. Three types of lung cancer evaluated (squamous cell carcinoma, adenocarcinoma, and bronchioalveolar carcinoma) together account for 65?70% of diagnoses. Accuracy achieved supports hypothesis that an accurate predictive model is generated from training images, and performance achieved is an accurate baseline for the process's potential scaling to larger datasets. Feature vector performance is good or better than Thiran and Macq's in every case. Except bronchioalveolar carcinomas, each individual cancer classification task experienced improvement, with two groupings showing nearly 20% classification accuracy.